The Influence Of The Demonstration Method On Students’ Ability To Write Procedure Text At SMP Negeri 5 Pematang Siantar - Ridwin Purba; Tiodora Fermiska Silalahi; Novelin Azhari Purba (Program Studi Pendidikan Bahasa Inggris FKIP, 2024)
This study aims to explain the effect of the demonstration method on the ability to write procedural texts for grade VII students of SMP Negeri 5 Pematang Siantar. The study used a correlational approach method. The data collection technique in this study is a test in the form of an essay and is divided into 2, namely Pre-test and Post-test. The data processing technique in this study is correlational. The results of this study were obtained from the results of pre-test and post-test data. The results of the pre-test data obtained with the number of 4501 with the lowest value of 65 and the highest value of 82, the average obtained was 72.5. The results of the post-test data obtained with the number of 4903 with the lowest value of 70 and the highest value of 90, the average obtained was 79.08. The result value using the correlational formula is 0.71. The final data results of testing the t-test hypothesis were obtained tcount 0.36 = at a significant level a = 0.05 and degrees of freedom (dk) = n – 2 or 62 – 2 = 60 obtained ttable = 2.00 so tcount is greater than ttable (tcount 1.671 ttable = 2.00) tcount Ha is accepted and Ho is rejected